TUNJANGAN PROFESI SEBAGAI UPAYA PENINGKATAN KOMPETENSI GURU UNTUK MEWUJUDKAN GURU PROFESIONAL - Yuliandri, Jimmi; Tahrun, Tahrun (Graduate Program Magister Manajemen Pendidikan, 2017)
This research was conducted to reveal the improvement of teachers’ competence who have received professional allowances in realizing professional teachers. The data were obtained through interviews, documentation and observation. Improving the teachers’ competence is expected in order to improve the quality of education. Only then the professional teacher is capable of conducting learning and succeeding in bringing the learner into the world of life according to today’s needs and challenges. Conversely, the unwillingness and inability of teachers to adjust their insight and competence with the demands of the development would be one of the obstacles to the achievement of educational and learning objectives. Keywords: Professional Allowances, Improvement of Teachers’ Competence, Professional Teacher